Новые виды цикадок рода эдвардсиана - Edwardsiana Zachv. (Homoptera, Auchenorrhyncha) из Приморского края - Ануфриев, Г.А. (Вестник зоологии, 1968)
The article contains the descriptions of five new species from genus Edwardsiana Zachv. (E. rubens, E. rubicunda, E. euphrosyne, E. aglaie, E. thalia, ssp. n.) living at various species of genus Ulmus in the Primorye. A table for their determination is given.